The Students' Perception On Youtube Video Speaking Project - Purnama, I Gusti Agung Vony; Krisnawan, Gusti Ngurah Aditya (International Journal of Linguistics and Discourse Analytics, 2024)
In language learning, there are four skills that must be mastered by the learners, such as speaking, reading, listening, and writing. Each of them has its own difficulty, particularly for EFL learners. This study is focused on speaking skill. Speaking English for the English as a foreign language students is difficult, since this skill is a real-time action, it means that the speakers must think fast to find the suitable vocabularies then use the correct pronunciation to convey the messages that they want to deliver. Thus, this present study aims to find out the students’ perception regarding their YouTube video speaking project in English II subject. This study applied a qualitative descriptive method. The data was collected from the interview. There were fourteen students participated on the interview. This can be concluded that the students have positive perception regarding their YouTube video speaking project. The finding shows that speaking English is important for them, they usually learn to speak from internet, particularly from YouTube videos. This speaking project was motivating them to be fluent in speaking English, improving their pronunciation in speaking, adjusting articulation and sentences to be able to convey English according to the sentence, and speaking in front of the camera. It is hoped that this result can facilitate the next researchers in the same area